Hepatite C crônica e manifestações cutâneas : experiência no acompanhamento conjunto (dermatologia/hepatologia) dos pacientes em tratamento para hepatite C - Capeli, Rafaela Lorenzon de Aragão (2015)
Background: Extrahepatic manifestations.are numerous in chronic hepatitis C. Among them, cutaneous symptoms or findings are frequent and may be a clue to underlying HCV infection. Porphyria cutanea tarda, lichen planus and mixed cryoglobulinemia are some examples. The therapy available in Brazil presents many side effects such as anemia, leukopenia, dermatitis, alopecia, pruritus and may induce diseases such as sarcoidosis. Objective: To describe dermatological findings in chronic hepatitis C patients treated with interferon alpha pegylated and ribavirin with or without telaprevir or boceprevir. Patients and methods: Choronic hepatitis C patients treated at the hepatology outpatient clinic of the Hospital Universitario Cassiano Moraes (HUCAM), in Vitoria, ES., candidates for the treatment with a combination of interferon alpha pegylated and ribavirin with or without telaprevir or boceprevir. All patients were submitted to a standard questionnaire and to a complete dermatological evaluation prior to the treatment and reassessed after start therapy. Results: Thirty five (70%) out of 50 patients had skin findings prior to the treatment. The most common was the pruritus without cutaneous lesions (40%), followed by psoriasis and porphyria cutanea tarda. The degree of pruritus was related to liver fibrosis, genotype and viral load, but with no statistical correlation. After starting treatment, 37 (74%) patients showed alterations at Interferon injection sites. Nine (18%) developed drug reactions (one palpable purpura, one drug retaled vasculitis andseven drug rash). Eight (16%) patients presented telogen effluvium, six (12%) had oral aphthous ulcers, three (6%) recurrent herpes labialis and three (6%) angularis cheilitis angularis. Discussion and Conclusion: In agreement with literature the study found this dermatological findings prior to the treatment: pruritus, cutaneous xerosis, psoriasis and porphyria cutanea tarda. Itching was the most frequent finding in the study, justifying systematic investigation for hepatitis C in patients with this complaint. Adverse drug reactions observed were well tolerated without need for treatment discontinuation. Hepatitis C is a silent disease, in which most cases progress to liver cirrhosis and hepatocarcinoma. Therefore, we should intensify investigations in extrahepatic manifestations which will facilitate early diagnosis of Hepatitis C.